Satiric modernism - Rulo, Kevin (Clemson University Press, 2021)
"Satiric Modernism reimagines the history and aesthetics of modernism through the lens of satire through provocative new readings of familiar texts and the introduction of largely unknown works. Kevin Rulo remaps the last hundred years as an era marked distinctively by a new kind of satiric critique of modernity"--